A multi-criteria decision analysis of alternative fuels for the - Månsson, Stina (My University, 2017)
This study assesses the prospect of renewable fuels in the shipping sector by conducting a multi-criteria decision analysis of selected alternative fuels with a panel of stakeholders. This provides an initial assessment of the importance of different factors influencing the choice of alternative marine fuel from a stakeholder perspective. Four alternative marine fuels, liquefied natural gas (LNG), methanol produced from natural gas (NG-MeOH), methanol produced from biomass (Bio-MeOH), and hydrogen produced from electrolysis by wind power (Elec-H2), are assessed towards 10 criteria using the analytic hierarchy process. The panel of stakeholders judging the importance of criteria valued economic criteria highest, followed by social criteria, environmental criteria and technical criteria. The relative importance between the criteria are not large, and the most preferred alternative marine fuel turned out to be electrolytic hydrogen from renewable energy sources when considering the joint preference of the stakeholders. The ranking order of fuels changes to some extent when different actors alone judge the importance of criteria, but electrolytic hydrogen turned out to be the most preferred option in most cases. However, international collaboration and technology specific policies and subsidies are most likely needed, and new infrastructure must be built, if electrolytic hydrogen is to be the dominating marine fuel in the future.
Keywords: Energi; Transport; Hållbar utveckling; Miljövetenskap; Energy; Transport; Sustainable Development; Environmental Sciences